Consumer Satisfaction towards the 9 Marketing Mix Elements (9P) of Fresh Strawberries at the Strawberry Picking Agro-Tourism of Lumbung Stroberi in Raharjo Village-Owned Enterprise Batu City East Java - Novi Haryati; Muhamad Zahran Nurirrozak; Putra Irwandi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
Lumbung Stroberi is one of the agriculture-based agro-tourism which is a business unit of Bumdes Raharjo, Batu City, Malang. Since its establishment in 2019, Lumbung Strawberry has focused on selling products and services. Product sales are packaged strawberries while services are educational tourism with the concept of picking strawberries. Business developments show that consumer behavior determines the sales and marketing success of this educative tourism. Therefore, this research aims to determine the level of consumer satisfaction with the marketing mix for strawberry products in Lumbung Straberi Bumdes Raharjo. This research uses a descriptive quantitative approach and was conducted in June - August 2022. This research used a descriptive quantitative approach and was conducted in December 2021-February 2022. This research used an online questionnaire with the Google Form tool. The research method used is Importance Performance Index and Customer Satisfaction Index. The research respondents were 60 people using purposive sampling method and processed using SPSS 26 and Microsoft Excel. This study uses an error tolerance or alpha of 0.5. There are 3 variables used in this research, namely Marketing Mix Performance Level (X1) and Marketing Mix Importance Level (X2) as independent variables and Consumer Satisfaction (Y1) as the dependent variable. The research results show that the overall level of consumer satisfaction (based on the CSI value) is 0.82 and is in the range of 0.81-1.00, which indicates that the visitor satisfaction index is the "Very Satisfied" criterion. This value is included in the good category. This explains that the majority of consumers are very satisfied with the performance of the marketing mix attributes (9P) carried out by Lumbung Straberi in general.